Diseño y elaboración de material didáctico en kichwa para el aprendizaje de Lenguaje y Literatura en el Octavo Año de Educación General Básica, en la Escuela Domingo Faustino Sarmiento, de la Parroquia San Juan de Ilumán, Cantón Otavalo. - Ipiales Quinchiguango, Mirian Yolanda (2015)
"Securing an education with cultural belonging to the peoples and nationalities in their own language and respecting their rights". (LOEI) In compliance with this obligation of the Organic Law of Intercultural Education, this research aims to contribute to the process of learning the value of mother tongue from the first level of education. Process that applies in different subjects of the current curriculum today. In this paper a contribution to the area of language arts to practice both languages Kichwa and Castilian is provided. Every area of knowledge requires a fundamental support which enable greater understanding of it, in this case have made teaching materials for 8th EGB, for each curricular area (6 materials) in both languages. According to research conducted let me point out that the school lacks teaching materials in Kichwa therefore this work we want to encourage the teaching processing and use. This research is based on educators as Piaget, Ausubel, Montessori, as major, who talks about the importance and benefit of teaching materials in meaningful learning of students.